Optimum formulation of aluminized anfo for blatings in underground mining - Giraldo Paredez, Emiliano Mauro (2020)
Drilling and blasting in a mining operation is essential, since the efficiency of subsequent operations depends on it. However, blasting also has negative effects, which can be minimized by selecting explosives according to the rock type. The most commonly used explosive is the ANFO, whose power can be regulated, adding aluminum in different percentages depending on the rock type (according to Bieniawski or Barton classification). To carry out this study, blasting tests were carried out in the Condestable Mine, with ANFO aluminized up to 6% of powdered aluminum, carrying out the loading of drills with compressed air at 80 PSI of pressure and priming with cartridge emulsion, under these conditions, linear charge concentrations and total charge per hole were determined. From the analysis of 20 parameters, it is concluded that the optimal formulation of aluminized ANFO for primary blasting in A, B1, B2 and C stopes in Condestable is 4% aluminized ANFO, where the rock types are class II and III- II. In addition, it is determined that the percentage of aluminum added to ANFO is directly related to the type of rock.